2019
DOI: 10.1108/medar-12-2017-0253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adopting IFRS 10 and IFRS 11 on consolidated financial statements

Abstract: Purpose The purpose of this paper is to investigate how the adoption of IFRS 10 and IFRS 11 affected consolidated financial statements. Specifically, the paper explores whether entities adopted mandatorily or voluntarily both IFRS, whether expressly declared effects, whether considered those effects as material and whether those effects had impacts on selected items of financial statements and on selected financial ratios. Design/methodology/approach The research is an exploratory study using public entities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The improvement of the literature throgugh a study by (Lopes, 2019) on the effects of the adoption of IFRS 10 and IFRS 11, have been previously assessed in France, Germany, and the United Kingdom, for some consolidated accounts and rates financila institutions. Thus, as is well known, there is still no robust post-adoption analysis (global sampling, by country and by sector of activity) of the effects of the adoption of these standards in these three countries.…”
Section: Figure 1 Fundamental Qualitative Characteristicsmentioning
confidence: 99%
“…The improvement of the literature throgugh a study by (Lopes, 2019) on the effects of the adoption of IFRS 10 and IFRS 11, have been previously assessed in France, Germany, and the United Kingdom, for some consolidated accounts and rates financila institutions. Thus, as is well known, there is still no robust post-adoption analysis (global sampling, by country and by sector of activity) of the effects of the adoption of these standards in these three countries.…”
Section: Figure 1 Fundamental Qualitative Characteristicsmentioning
confidence: 99%
“…The future research may apply comparison with equivalent standards in IFRS. The expected research may include the following points: measure the effects of adopting AAOIFI (FAS-23) on consolidated financial statements for IFIs (Lopes and Lopes, 2019) and compare with IFRS-10; compare the updated versions of Sukuk (FAS-33 and FAS-34) with conventional bonds to see to what extent the updates and improvements in AAOIFI standard added value for the presentation of FS; and measure the impact of applying FAS-30 for impairment and credit losses and onerous commitments over the IFIs after Covid-19 pandemic and compare with IFES-9 related to expected provisions. There are additional issued standards asking further researches as follows: FAS-28 for Murabaha and other deferred payment sales; FAS-31 investment agency and FAS-32 Ijarah Between 2018 and 2020, AAOIFI issued new five governance standards as follows: GSIFI-8 Central Shari’ah Board; GSIFI-9 Shari’ah compliance function; GSIFI-10 Sharia; compliance and fiduciary ratings for Islamic financial institutions; GSIFI-11 internal; Shari’ah audit; and And GSIFI-12 Sukuk governance. …”
Section: Recommendations and Directions For Future Researchmentioning
confidence: 99%
“…measure the effects of adopting AAOIFI (FAS-23) on consolidated financial statements for IFIs (Lopes and Lopes, 2019) and compare with IFRS-10;…”
Section: Recommendations and Directions For Future Researchmentioning
confidence: 99%
“…10 While the main objective of the new standard is to reduce diversity in practice regarding the application of the control definition and improve financial information comparability (IASB, 2011), there is limited empirical evidence to support its effectiveness. Lopes and Lopes (2019) undertake an exploratory study of the effect of IFRS 10 in Germany, France and the UK and find few firms report IFRS 10 adoption had a material impact on their financial statements. Whilst Ben-Shahar et al (2016) assess the validity of the standard from an economic perspective, they do not undertake any empirical or descriptive analysis of the effects of IFRS 10.…”
Section: Institutional Settingmentioning
confidence: 99%
“…This study is motivated by the lack of empirical evidence on how firms responded to the adoption of IFRS 10, as current evidence is limited to an exploratory study (Lopes and Lopes, 2019). The IASB indicated that most consolidation decisions would be unaffected by the new control definition and expressed uncertainty as to whether the revised control definition would result in the consolidation of more or fewer investees (IASB, 2011, p. 17).…”
Section: Introductionmentioning
confidence: 99%